2014
DOI: 10.5572/ajae.2014.8.2.089
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Enhancement of Particle Removal Efficiency in Spray Tower Scrubber Using Electrospray

Abstract: There have been a lot of efforts to keep permissible emission standards and to reduce the amount of emitted air pollutants. There are several air pollution control equipments, however, wet scrubber is used to remove particulate matters and gaseous pollutants simultaneously, even if it has low collection efficiency in the particle size less than 5.0 μm. To overcome this problem, we introduced a spray tower scrubber with an electrospray system which a high voltage was indirectly applied. We found that collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Figure 4c also shows that the collection efficiency of particles that were less than 2 μm in diameter was larger than 60% based on a water consumption of 45 L/hr. When the gas velocity was 2.7 m/sec, the corresponding liquid-to-gas mass ratio (L/G) was 0.022 kg/kg, which is advantageous compared with other treatment processes (Carotenuto, Natale, and Lancia 2010;Kim et al 2014;Natale et al 2015;Tsai et al 2005), as shown in Table 3.…”
Section: Effect Of Spray Volumementioning
confidence: 99%
“…Figure 4c also shows that the collection efficiency of particles that were less than 2 μm in diameter was larger than 60% based on a water consumption of 45 L/hr. When the gas velocity was 2.7 m/sec, the corresponding liquid-to-gas mass ratio (L/G) was 0.022 kg/kg, which is advantageous compared with other treatment processes (Carotenuto, Natale, and Lancia 2010;Kim et al 2014;Natale et al 2015;Tsai et al 2005), as shown in Table 3.…”
Section: Effect Of Spray Volumementioning
confidence: 99%
“…Moreover, spray units are being installed within a prilled tower or wet scrubber to reduce the emissions of urea or PM 2.5 [186] . The application of electro-spray in a spay tower helps in removing the particulate matter <5μm having a ratio of liquid to the gas flow rate of 41-84% for an average particle diameter of 0.3μm [187] . One of the scientific research articles shows that by adopting the spray mechanism, the rain shower model is developed for sustainable and low-cost removal of CO 2 and PM 2.5 [188] .…”
Section: Probable Engineered Technologies For Control Of Aerosol Cum mentioning
confidence: 99%
“…Breakage of water droplets under an electric force has proved to be a highly efficient atomization route. It enables the droplet diameter to decrease by 50% while increasing the specific charge four times compared with a conventional mechanical atomized spray. , Charged atomization has been utilized for technical upgrades on particle capture in wet scrubbers, improving collection efficiency by 20–40% , and reducing the water consumptions . This treated method enables the formation of charged droplets with a small diameter, high density, and large relative velocity in a particle-gas flow field , and thus deserves research on particle capture but has been rarely mentioned in the literature for WESP performance improvement.…”
Section: Introductionmentioning
confidence: 99%